THE EFFECT OF OPERATING PROFIT MARGIN AND TOTAL ASSET TURN OVER ON RETURN ON ASSETS AT PT. ADHI KARYA (PERSERO) TBK. PERIOD 2012-2021 - Widiawati Widiawati; Mila Badriyah; Puspa Miranti (UIN Sunan Gunung Djati Bandung, 2023)
AbstractThis research is motivated by the fluctuating value of Return On Assets, whereas it is well known that profitability is a measure of a company's success in managing a company. Therefore the researchers conducted a study that allegedly influenced Return On Assets, namely Operating Profit Margin and Total Asset Turn Over. The purpose of this study was to determine how much influence Operating Profit Margin (OPM) and Total Asset Turn Over (TATO) have on Return On Assets (ROA) partially and simultaneously. The method used in this research is descriptive method with a quantitative approach. The results of the study concluded that the test results of the analysis of the coefficient of determination of the Operating Profit Margin partially did not have a significant effect on Return On Assets of 6.7%. Meanwhile, Total Asset Turn Over has a partial but not significant effect on Return On Assets of 90.3%. Thus, Operating Profit Margin and Total Asset Turn Over simultaneously have an effect but not significant on Return On Assets of 95.9%.Keywords: Operating Profit Margin, Total Asset Turn Over, Return On Asset